Дисфункция эритроцитов в условиях нитроксидативного стресса при развитии сосудистой патологии. - Рамазанов, В.В.; Воловельська, Є.Л.; Ніпот, О.Є.; Єршов, С.С.; Єршова, Н.А.; Руденко, С.В.; Рязанцев, В.В.; Бондаренко, В.А. (Експериментальна і клінічна медицина, 2018, - Т. 79-80, № 2-3, С. 50-56., 2018)
The prospects of developing several pharmacological strategies related to detoxification of peroxynitriteand inhibition of the nitration of protein tyrosines by this nitroxidant are being considered. An increase inthe level of nitrotyrosine is a consequence of the pathogenic mechanism of superoxide-induced endothelialdysfunction observed in various diseases. A significant part of peroxynitrite is neutralized by erythrocytes;however, with nitroxidative stress, their dysfunction develops, which can contribute to micro- andmacrovascular diseases. In this aspect internal erythrocyte dysfunction can be the object of attention forinvestigating the possibility of developing a pharmacological strategy for stimulating the antioxidantpotential of red blood cells
DYSFUNCTION OF ERYTHROCYTES IN THE CONDITIONS OF NITROXIDATIVE STRESSIN THE DEVELOPMENT OF VASCULAR PATHOLOGY
Рамазанов ВВ, Воловельская ЕЛ, Нипот ЕЕ, Ершов СС, Ершова НА, Руденко СВ, Рязанцев ВВ, Бондаренко ВА. Дисфункция эритроцитов в условиях нитроксидативного стресса при развитии сосудистой патологии. Експериментальна і клінічна медицина. 2018; 79-80 (2-3): 50-6
Keywords: эритроциты; сосудистая патология; нитроксидативный стресс